DESIGN OF POLTEKSMART TRASH BIN: SOLUTION FOR WASTE MANAGEMENT IN AVIATION TRAINING COLLEGE - Ramadhani, Muhammad Ichsan; Febriansyah, Fadly; Martadinata, M Indra; Primadewi, Betha Agus (Journal of Airport Engineering Technology (JAET), 2024)
Waste management issues are a significant challenge in many major environments, including dormitory life in aviation vocational colleges. This study aims to design a prototype of a Polteksmart trash bin equipped with sensors and a Telegram Bot to manage waste in the dormitory building at Politeknik Penerbangan Palembang. This research and development (R&D) method using a 4D model started with data collection from literature review and observation. The research result is an innovative design of a robot trash bin equipped with infrared sensors, proximity sensors, RTC sensors, EM4, and a Telegram Bot that sends notifications to mobile phones whenever trash capacity reaches 90%. A material expert and IT expert have validated the final design, and the analysis becomes quantitative data with assessment results of 90%, which means it is very innovative and can be implemented. By implementing it, we hope to increase the effectiveness and efficiency of the waste sorting and management system. This implementation not only helps reduce operational costs but also supports efforts to recycle and reuse organic waste, which with the goal of creating a cleaner and healthier environment in the Politeknik Penerbangan Palembang. This research emphasizes the importance of technology integration in providing real-time waste management by making it easier for users to monitor the condition of the bins. As such, this research provides a strong foundation for future research to improve waste management's efficiency and effectiveness in educational settings.